Comparison of Various Means of Evaluating Molecular Electrostatic Potentials for Noncovalent Interactions. Issue 9 (30th October 2017) - Scheiner, Steve
Abstract : The various heterodimers formed by a series of Lewis acids with NH3 as Lewis base are identified. Lewis acids include those that can form chalcogen (HSF and HSBr), pnicogen (H2 PF and H2 PBr), and tetrel (H3 SiF and H3 SiBr) bonds, as well as H‐bonds and halogen bonds. The molecular electrostatic potential (MEP) of each Lewis acid is considered in a number of ways. Pictorial versions show broad regions of positive and negative MEP, on surfaces that vary with respect to either the value of the chosen isopotential, or their distance from the nuclei. Specific points are identified where the MEP reaches a maximum on a particular isodensity surface ( V s, max ). The locations and values of V s, max were evaluated on different isodensity surfaces, and compared to the stabilities of the various equilibrium geometries. As the chosen isodensity is decreased, and the MEP maxima drift away from the molecule, some points maintain their angular positions with respect to the molecule, whereas others undergo a reorientation. The lowering isodensity also causes some of the maxima to disappear. In general, there is a fairly good correlation between the energetic ordering of the equilibrium structures and the values of V s, max . A number of possible Lewis acid sites on the heteroaromatic imidazole ring were also considered and presents some cautions about application of V s, max as the principal criterion for predicting equilibrium geometries. © 2017 Wiley Periodicals, Inc. Abstract : Various facets of the molecular electrostatic potential (MEP) are examined and compared with one another, as predictors of the binding energy calculated with a partner molecule. The maximum of the MEP can be computed on each of several different isodensity surfaces, just as pictorial versions of the MEP can be evaluated at a number of distances from each nucleus. These comparisons were made for systems containing H, halogen, chalcogen, pnicogen, and tetrel bonds.